How Teacher Educators' Lived Experiences Affect Teaching for Social Justice1. Issue 4 (28th September 2022) - Menna, Lydia; Dharamshi, Pooja; Kosnik, Clare
Abstract: This article explores the ways in which lived experiences informed literacy teacher educators' (LTEs) pedagogies and practices of social justice. In particular, three case studies were conducted to examine why the LTEs chose to address social justice, as well as how their life experiences influenced their views and pedagogies in their literacy courses to address social justice, race, and race related issues. Each of the LTEs recalled transformative experiences that shaped their views not only of literacy, but the interconnections between schooling, social justice, and race.